Medial Plantar Flap for Skin Defects of the Weight-bearing Area of the Foot - Kanaya, Fuminori; Kiyama, Katsuhiko; Sunagawa, Hideyuki; Futenma, Chojo; Oshiro, Wataru; Ibaraki, Kunio (Orthopedics & Traumatology, 1999)
The weight-bearing area of the foot is covered by thick, stable, and tough glabrous skin. In 6 patients, we covered the skin defect of the weight-bearing area with either pedicle or free medial plantar flaps. The patients' age ranged from 16 to 55 years old (mean 34 years old). Skin defects were located at the forefoot in 3 and at the heel in 3. The size of the flaps ranged from 6.5×5cm to 16×10cm. There were 5 free vascularized flaps and 1 pedicle flap. In 2 free flaps, nerve to medial plantar skin was not repaired. All flaps survived completely and 5 out of 6 flaps recovered some sensation. One patient who did not recover sensation in the free medial plantar flap produced ulcers at 2 years and 3 years-2months after surgery. These ulcers healed without sequele recurrence after debridement and closure. We think that the medial plantar flap is the treatment of choice for the coverage of weight-bearing area, and sensory recovery is needed to prevent ulcer formation.